Adoption of One-Touch Emergency Alert Apps: User Authentication, Simplicity, and Trust for Human Safety - Ravikant Nanwatkar; Girase Chirag; Vaidya Omkar; Chavan Sanket; Shelke Shaharam (International Journal of Mobile Computing Technology, 2026)
Quick reactions to disasters are extremely important to the safety and health of people. Nonetheless, another frequent problem with emergency cases is the time lag between reports of the incidents and the success and timely response of the concerned authorities. Mobile-based emergency alert systems have thus come in as a potential solution to this problem, given that they enable straightforward and direct communication between the citizens and the law enforcement agencies. This paper introduces the idea and creation of a one-touch emergency alert application, which has a high degree of user authentication, user-friendliness, and reliability. The application that is proposed would make users register with essential identity information, including their full names and mobile phone numbers. The user can activate an alert with just one touch in case there is an emergency, and this will automatically alert the police or emergency response staff who are within the vicinity. The alert shows the verified identity of the user and the real-time location, therefore reducing the efforts of the user and making the alert authentic. Such a strategy not only accelerates the process of seeking aid, but it also aids in the minimization of the abuse of emergency services. The paper also examines the considerations in designing the system, which forms the backbone of the system, such as the trade-offs between the need to provide strong security and the need to be user-friendly, particularly in high-stress situations. It also highlights the need to focus on user trust and data privacy as a way of persuading adoption. Finally, this paper shows that the one-touch emergency alert applications can increase the level of safety among people, improve the effectiveness of police officers in responding to emergencies, and inspire more individuals to become more confident in the use of digital safety devices.
Keywords: Ease of use; emergency communication; emergency usability; human safety; one-touch emergency alert; rapid response system; real-time location tracking; user authentication; user trust; victim support